The Issue of Ensuring Reasonable Period for Appellate Proceedings in Administrative Trials - Badalyan, Sayad (Bulletin of Yerevan University C: Jurisprudence, 2024)
The issue of simplifying the appellate proceedings and reducing the workload of the appellate court is currently one of the most relevant issues in the field of administrative trials. The study of judicial statistics proves that the period between the appeal being accepted for proceedings and the date of the first court hearing of the appeal is about 1.5 years on average. Moreover, this period tends to increase constantly. Excessively long periods for examining cases violate the rights to a fair trial within a reasonable time and effective judicial protection of rights and freedoms, as defined respectively in the Articles 63 and 61 of the RA Constitution, as well as the Articles 6 and 13 of the European Convention For the Protection of Human Rights and Fundamental Freedoms. Moreover, the European Court of Human Rights considers the unnecessarily long periods of examination of cases as evidence of the poor functioning of the judiciary. The State is not only responsible for any unnecessary delay in the trial, but it is also the latter’s obligation to reform the judiciary so that to overcome the issue of overloading the judiciary as a result of repeated but numerous cases. During past years an attempt was made to settle the subject issue by increasing the number of judges of the appellate court, but the practice shows that it did not bring the desired results. In such conditions the solution to the matter should be gained through the simplification of judicial procedures. Taking into account the foregoing, the article covers a number of procedural tools for reducing the workload of the appellate court (for example, limiting the right to appeal in a certain category of cases or establishing the requirement to obtain a prior court permission to file an appeal), the implementation of which in the Code of Administrative Procedure can significantly contribute to solving the issue.